Effect of Formaldehyde Inhalation on Leukocyte Counts and Malondialdehyde Levels in Wistar Rats (Rattus norvegicus) - Muhammad Fauzan; Ima Arum Lestarini; Anak Agung Ayu Niti Wedayani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Formaldehyde is a chemical compound that is often found in everyday life, such as in the chemical industry to research laboratories. Formaldehyde has toxic properties that can harm humans in long term exposure. The genotoxic and cytotoxic properties of formaldehyde can cause oxidative stress. This study assesses the number of leukocytes and levels of malondialdehyde in Wistar rats induced by 40 ppm formaldehyde. This study used 12 Wistar rats taken at random and put into 2 groups, namely the control and treatment groups. The treatment group was given formaldehyde inhalation at a concentration of 40 ppm for 16 weeks. At the 16th week, rat blood was taken retroorbital to calculate the number of leukocytes and levels of malondialdehyde. The calculation results were then tested statistically using IBM SPSS Statistics 25 software. The results showed that there was no significant difference (p>0.05) between the number of leukocytes in the control group and the treatment group. This study also showed that there was a significant difference (p<0.05) between malondialdehyde levels in the control group and the treatment group. In conclusion, there was no effect of formaldehyde induction with a concentration of 40 ppm on the number of leukocytes and there was an effect of formaldehyde induction with a concentration of 40 ppm on malondialdehyde levels in Wistar rats.